(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The low quality of education aimed at the intellectual formation of citizens has been a real impasse in the construction of citizenship. Massive investments in training individuals without the least concern for the efficiency of education offered by the state only manipulate and deceive public opinion on state action. Education, a social right, constitutionally guaranteed in our country, has long been nothing more than a rhetoric of political discourse. Public policies aimed at education have the objectives of presenting numbers and not effectively forming citizens capable of understanding the complex political-social-economic system today. The individual is read of the enjoyment of a full citizenship, now only declared in the constitutional text.